Prostaglandin E(2)-EP3 Axis in Fine-Tuning Excessive Skin Inflammation by Restricting Dendritic Cell Functions - Shiraishi, Noriko (Public Library of Science, 2013)
Prostaglandin E(2) (PGE(2)) is produced in the skin and is suggested to play a role in the regulation of cutaneous immune homeostasis and responses. However, the multifaceted functions of PGE(2) continue to elude our understanding, especially because of the multiplicity of PGE(2) receptors—EP1, EP2, EP3, and EP4. While cAMP-elevating EP4 is known to activate the functions of cutaneous dendritic cells (DCs), including Langerhans cells (LCs) and dermal DCs, the role of cAMP-suppressing EP3 in this process remains unknown. Here we demonstrated that an EP3 receptor selective agonist, ONO-AE-248, inhibited chemotaxis and co-stimulatory molecule expressions of DCs in vitro. A suboptimal dose of antigen was sufficient to induce contact hypersensitivity in EP3-deficient mice. Intriguingly, EP3 deficiency did not impair skin inflammation at all when the antigen dose was sufficiently high. EP3 limited the functions of cutaneous DCs only when the antigen dose was low. In contrast to EP4, the observed unappreciated function of EP3 may stabilize the cutaneous DCs to halt the impetuous response to a suboptimal dose of antigen. Taken together, PGE(2)-EP3 signaling is essential for fine-tuning excessive skin inflammation by restricting DC functions.